การพยากรณ์อัตรามรณะไทยด้วยตัวแบบโลจิสติกส์ - จักรกฤษณ์ ศรีทองดี (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
This research aims to forecast the mortality rate of Thai population in the next 20 years by using forecasting methods: Lee-Carter Model and Logistic Regression Model. Data used in the study are the number of population and the number of death by age and sex of year 1999 - 2009 from the Ministry of Interior and the Ministry of Public Health respectively. In addition to comparing the estimated mortality rates from all methods to find the model that is most appropriate using mean absolute percentage error (MAPE). Moreover, this research attempts to finds the relationship between the predicted mortality rates and the mortality rates of insured lives in Thai Mortality Table (TMO) with mortality improvement scales. The results show that all models have the predicted mortality rates for the next 20 years in the same direction and trend to decrease over time for both males and females. The predicted mortality rates of males are slightly higher than those of females. The comparison of the estimated mortality rates showed that the Lee-Carter model provides the most minimum MAPE for both males and females. Moreover, it reveals that the mortality rates for insured lives of mortality improvement scales have a decrease trend over time.